THE ROLE OF THE CAPITAL ADEQUACY INDEX OF THE CAMELS STANDARD IN ACHIEVING THE REQUIREMENTS OF BANKING GOVERNANCE, A STUDY OF A SAMPLE OF IRAQI COMMERCIAL BANKS - Assist. Prof AkeelDakheel Kareem; RuselGhalibUhmedy (Scholar Express Journals, 2023)
The research aims to define the capital adequacy index and the standard ratio determined by the Central Bank of Iraq based on and in line with the decisions of Basel 3, and the role of this indicator in protecting depositors' money as well as evaluating the performance of banks with the capital adequacy index and indicating its impact on achieving the requirements of banking governance
Keywords: CAMELS standard; capital adequacy; banking governance; banking risks.